PERFORMA BAHASA INDONESIA DARI SEGI PENGGUNAAN STRUKTUR KALIMAT BUPATI DI SUMATERA BARAT DALAM YOUTUBE - Alvionita, Feni; Ermanto, Ermanto; Agustina, Agustina (Jurnal Bahasa dan Sastra, 2018)
This study was conducted to describe the Indonesian language in terms of using sentence structure by regent in West Sumatera (Regent of Dharmasraya, Regent of Pesisir Selatan, Regent of 50 Kota, Regent of Agam, Regent of Pasaman Barat, Regent of Pasaman, Regent of Sijunjung, Regent of Solok Selatan, and Regent of Mentawai) in Youtube. This study is a qualitative study using descriptive method. The data in this study is a sentence obtained from the speech of regent in West Sumatra. The data collection are as follows, (1) to identify speech of regent in West Sumatera which is included in the Indonesian language performance in terms of using the regent's sentence structure in West Sumatra, (2) transcribing the speech of regent in West Sumatra which has been downloaded through Youtube, (3) observingÂ  and giving the data code. Technique of data validation in this study is using technique of detail description while describing or explaining the detail data to be analyzed. Techniques of data analysis in this study are as follows, (1) identifying data, (2) classifying data, (3) interpreting data, and (4) concluding data. The conclusion of this study is the Indonesian language in terms of using sentence structure by the regent in West Sumatra in Youtube. The statement is proved by the speech of using the appropriate sentence structure as much as 299 sentences with 84% percentage and incorrect as much as 58 sentences with a percentage of 16%. In other words, the performance of the Indonesian language in terms of using sentence structure in this study is dominated by the accuracy of its use.keywords: sentence,Â  sentence structure, regent, Youtube